Metastasis from Gastric Carcinoma Causing Ureteral Obstruction (Indian Journal of Case Reports, 2017)
Gastric carcinoma rarely metastasizes to the lower urinary tract. Adenocarcinomas are commonly found in the stomach, however this histologic entity is rarely seen in the bladder and often difficult to distinguish primary from secondary with only histopathologic changes. We report a 61 year old man with a history of total gastrectomy for gastric adenocarcinoma presenting six months later with metastasis to the lower urinary tract. He presented with nonspecific symptoms and laboratory investigations showed progressive elevation of serum creatinine level. Despite implantation of double J stents, renal function did not improve. Computed tomography revealed enlarged mesenteric lymph node, bilateral hydronephrosis and hydroureter likely due to bladder wall thickening at the vesicoureteric junction. Retrograde pyelogram and biopsies taken from the bladder revealed secondary bladder adenocarcinoma. In summary, metastatic carcinoma of the lower urinary tract should be considered in patients with history of gastric adenocarcinoma whose presentation is consistent with ureteral obstruction.